Character Education Insertion through Acculturation ‘Kampung Madinah’: A Living Qur’an Study of Temboro Community, Magetan East Java - Huda, M. Dimyati; Hakamah, Zaenatul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This article presents an examination of the social behaviour and religious practices of the people of Temboro, Magetan, East Java. The religious behaviour of the Temboro community is the result of the integration of character education values based on the interpretation of Quranic texts (living Qur’an), which have been formed through the process of acculturation. Temboro Village is known as “Kampung Madinah,” exhibiting a culture analogous to that of Madinah City in terms of dress, religious rituals, and social ethics. This article employs a qualitative method with an anthropological approach to investigate the character education values embedded in the socio-religious and cultural practices of the Temboro community. Reception theory is used to analyse the findings, which reveal that the insertion of character education shapes the socio-religious behaviour of the Temboro community. This process is shaped by the informal rules of the kiai in Pesantren Al-Fatah Temboro. The character education that shapes the socio-religious behaviour of the Temboro community is socially constructed and embedded in the community through acculturation to the recitation tradition, social ethics and daily habits. Secondly, the behaviour and social religious attitudes of the Temboro community follow the interpretation of the Qur’anic text received from divine and human values. These values are controlled by religious authority and local wisdom.